Analisis Penerapan Perhitungan, Pemotongan Dan Pelaporan Pajak Penghasilan (PPh) Pasal 21 Pada PT. Askrindo Cabang Surabaya - Elisa Ayu Febryanti; Rr. Adiati Trihastuti (Jurnal Akuntan Publik, 2024)
Income Tax Article 21 is a tax imposed on the income of taxpayers. The purpose of this study is to analyze the application of the calculation, withholding, and reporting of Income Tax Article 21 derived from PT ASKRINDO Surabaya Branch. Income Tax Article 21 plays an important role in the context of taxation, especially in regulating the imposition of taxes on employee income obtained from the company. This research is motivated by efforts to avoid additional costs due to errors and delays in calculating, withholding, or reporting employee tax payments in accordance with Income Tax Article 21. The research method used in this study uses a descriptive method with a qualitative approach. The data sources used in this research are primary data and secondary data. The data was obtained by means of observation, interviews and documentation with informants from PT ASKRINDO Surabaya Branch. This research produces a conclusion that shows taxpayer compliance with Income Tax Article 21 is supported by the company's tax payment system. PT. ASKRINDO Surabaya Branch in the implementation of the calculation, withholding and reporting of Income Tax (PPh) Article 21 is in accordance with the current law.